Eksplorasi Alam Semesta: Mengintegrasikan Astronomi dalam Kurikulum Pendidikan Anak Usia Dini - Miratul Hayati; Desmaliza; Asbi, Sherllyn Azzaharra (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Introducing basic astronomy concepts early can help children develop a deeper interest and understanding of science in the future, yet it remains underexplored. This study aims to examine the methods and benefits of integrating astronomy into early childhood education (ECE) curricula and its impact on child development. Using a qualitative approach with a case study method, the research involved four (4) ECE teachers in Jakarta and Depok who teach astronomy to children. Data were collected through in-depth interviews and analyzed thematically. Findings show that children are highly enthusiastic about learning astronomy. Teachers employed creative and interactive methods such as picture stories, educational videos, and simple experiments. Adapting the material to the child’s developmental stage—such as using simple language and easily understood analogies—was key to successful learning. Astronomy education was found to support the development of critical thinking skills, curiosity, as well as children's social and collaborative abilities. The study concludes that integrating astronomy into ECE curricula holds great potential for supporting child development. It provides empirical insights into how astronomy can be effectively adapted for early childhood learning. Additionally, the research offers recommendations for educators and policymakers in designing more meaningful curricula.